Psychometric defensibility of the Social, Academic, and Emotional Behavior Risk Screener (SAEBRS) Teacher Rating Scale and multiple gating procedure within elementary and middle school samples. (October 2016) - Kilgus, Stephen P.; Eklund, Katie; von der Embse, Nathaniel P.; Taylor, Crystal N.; Sims, Wesley A.
Abstract: The primary purposes of this investigation were to (a) continue a line of research examining the psychometric defensibility of the Social, Academic, and Emotional Behavior Risk Screener — Teacher Rating Scale (SAEBRS-TRS), and (b) develop and preliminarily evaluate the diagnostic accuracy of a novel multiple gating procedure based on teacher nomination and the SAEBRS-TRS. Two studies were conducted with elementary and middle school student samples across two separate geographic locations. Study 1 ( n = 864 students) results supported SAEBRS-TRS defensibility, revealing acceptable to optimal levels of internal consistency reliability, concurrent validity, and diagnostic accuracy. Findings were promising for a combined multiple gating procedure, which demonstrated acceptable levels of sensitivity and specificity. Study 2 ( n = 1534 students), which replicated Study 1 procedures, further supported the SAEBRS-TRS' psychometric defensibility in terms of reliability, validity, and diagnostic accuracy. Despite the incorporation of revisions intended to promote sensitivity levels, the combined multiple gating procedure's diagnostic accuracy was similar to that found in Study 1. Taken together, results build upon prior research in support of the applied use of the SAEBRS-TRS, as well as justify future research regarding a SAEBRS-based multiple gating procedure. Implications for practice and study limitations are discussed.